Cross-sectional evaluation of clinical and immunological parameters at partially microgrooved vs machined abutments in humans - Gerhard Iglhaut; Sebastian Salomon; Tobias Fretwurst; Peter Thomas; Janina Endres; Selina Kessler; Burkhard Summer (SpringerOpen, 2021)
Abstract Objective The objective of the present study was to examine the clinical and immunological parameters in samples collected from the peri-implant crevicular fluid (PICF) of machined titanium (M) abutments compared to titanium abutments with a laser-microtextured surface (LMS) on dental implants. Material and methods A total of 40 patients with one titanium implant, half of them (n=20) provided with a M abutment (control group) and the other half (n=20) with LMS abutments (test group), were included in the study. Clinical parameters pocket probing depth (PD), full-mouth plaque score (FMPS), radiographic bone loss (RBL), clinical attachment level (CAL), mucosal recession (MR), bleeding on probing (BOP), and width of keratinized mucosa (KM) were evaluated. The peri-implant sulcus fluid was analyzed for cytokines IL-1α, IL-1β, IL-6, IL-8, and IL-10 via flow cytometry. Results Clinical evaluation demonstrated no significant difference of PD (mean LMS = 3.50 mm/SD 0.95 mm vs mean M = 3.45 mm/SD 0.76 mm (p=0.855)), MR (mean LMS = 0.30 mm/SD 0.57 mm vs mean M = 0.35 mm/SD 0.67 mm (p=0.801)), CAL (mean LMS = 3.60 mm/SD 1.14 mm vs mean M = 3.55 mm/SD 0.89 mm (p=0.878)), and KM (mean LMS = 2.03 mm/SD 1.08 mm vs mean M = 2.13 mm/SD 0.92 mm (p=0.754)) between LMS and M abutments. LMS abutments showed less BOP than M abutments (26.7% vs 30.8%), but statistically not significant (p = 0.2235). Radiographic bone loss (mean LMS = 0.22 mm/SD 0.44 mm vs mean M = 0.59 mm/SD 0.49 mm) was reduced in the test group in comparison with the control group (p=0.016). In the collected PICF, the levels of pro-inflammatory cytokines IL-1α (median LMS = 180.8 pg/ml vs M = 200.9 pg/ml (p=0.968)) and IL-1β (median LMS = 60.43 pg/ml vs M = 83.11 pg/ml (p=0.4777)) were lower, and the levels of IL-6 (median LMS = 180.8 pg/ml vs M = 200.9 pg/ml (p<0.0001)) were significantly lower in the test group. In contrast, the levels of IL-8 (median LMS = 255.7 pg/ml vs M = 178.7 pg/ml (p=0.3306)) were higher in the test group, though not significantly. The levels of anti-inflammatory IL-10 were significantly increased in the test group (LMS median = 0.555 pg/ml vs M median = 0.465 pg/ml (p=0.0365)). IL-1β showed a significant correlation to radiologic bone loss (p=0.0024). The other variables IL-1α, IL-6, IL-8, and IL-10 had no significant correlation to radiological bone loss. Conclusion Within the limitations of this study, titanium implants provided with laser-microtextured surface abutments seem to demonstrate less pro-inflammatory and more anti-inflammatory activity and to show reduced radiographic bone loss compared to machined titanium abutments. Clinical relevance The use of laser-microtextured surface abutments might have the potential to support peri-implant tissue health.